Rancang Bangun Kontrol Pemadam Kebakaran Menggunakan Sensor MQ-2 dan Flame Sensor 5 Channel Berbasis Fuzzy Logic - Ardin Fajar Tri Admaja; Edi Kurniawan; Dian Junita Arisusanty (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Fire is an event that often occurs due to human negligence. Losses from fire include damage to goods, business delays and can even cause loss of life. For early handling of fires, a "Fire Fighting Control Design Using MQ-2 Sensor and Fuzzy Logic Based 5 Channel Flame Sensor" has been created. This tool uses the MQ-2 sensor to detect gases related to fires, such as hydrocarbon gas. A 5 channel flame sensor is used to detect flames. The predetermined fuzzy logic rules will be used to control the fire extinguisher and implemented using the Arduino Atmega 2560 microcontroller as the brain of the system. Next, the microcontroller will send a control signal to the 12V DC pump output as a water spray system to deal with fires. The test results of this system show that the tool can detect early fire hotspots and respond well to fire extinguishing according to the fuzzy rule decisions carried out by testing the tool with 30 fire spots at different distances.